Bounds on coefficients of reciprocals of formal power series with rapidly decreasing coefficients. (28th December 2006) - Berenhaut, Kenneth S.; Allen, Edward E.; Fraser, Sam J.
Abstract : This paper studies reciprocals of formal power series whose coefficients are monotone and bounded by a geometrically decaying sequence. Explicit and applicable, optimal decay rates are provided for the coefficients of the reciprocal series in terms of the parameters of the geometric bound. The results imply a best possible lower bound on the zeros of the series being considered.